Efficiency of a High-dose Intravenous Immunoglobulin Therapy in Children with Autism Spectrum Disorders Associated with Genetic Deficiency of Folate Cycle Enzymes - Dmitry V. Maltsev (Journal of Global Pharma Technology, 2016)
Previously, it has been repeatedly reported on the effectiveness of intravenous immunoglobulin therapy in some children with autism spectrum disorders without specifying selection criteria of potential responders to immunotherapy. Objective: to evaluate high-dose immunoglobulin therapy efficacy and safety in children with autism spectrum disorders and genetic deficiency of folate cycle. The studied group consisted of 78 children aged 2 to 10 years who have been on intravenous immunoglobulin at a dose of 2 g/kg per month for 6 months. The control group included children of similar age and gender distribution, which received only non-drug rehabilitation support. The dynamics of psychiatric symptoms were assessed using the Aberrant Behavior Checklist scale. Complete elimination of the phenotype of autism spectrum disorders has been obtained in 21 patients and an improvement was marked in 33 children of study group. In parallel, positive dynamic of other clinical manifestations of folate cycle deficiency phenotype was evaluated: PANDAS (19 out of 21), epilepsy (29 out of 36) and gastrointestinal (in 49 out of 68 children) syndromes.  Intravenous immunoglobulin has a complex positive impact on the manifestation of a genetic deficiency of folate cycle, including autism spectrum disorders, extrapyramidal disturbances, bowel syndrome, epileptiform brain activity, immune deficiency, and leukoencephalopathy.Keywords: Folate cycle, Intravenous immunoglobulin, Autism spectrum disorder.